Place Making of Public Spaces Within Transit-Oriented Development (TOD): A Review - Nurul Syala Abdul Latip; Nur Zalilah Zulnaidi; Nabilah Redzuan; Mariana Mohamed Osman (Malaysia Institute of Planners, 2024)
Indexed by Scopus/MyCite